Let us assume the first even number = n The second consecutive even number = n + 2 The third consecutive even number = n + 4 The addition of the three consecutive even numbers is 42 and it is already given in the question. Based on the information's given in the question, the answer can be easily deduced. Then, the equation can be written as n + (n + 2) + (n + 4) = 42 3n + 6 = 42 3n = 42 - 6 3n = 36 n = 36/3 = 12 So The first even number = 12 The second consecutive even number = n + 2 = 12 + 2 = 14 The third consecutive even number = n + 4 = 12 + 4 = 16 So the three consecutive even numbers are 12, 14, 16.